Management of Behçet disease: a systematic literature review for the European League Against Rheumatism evidence-based recommendations for the management of Behçet disease. Issue 10 (17th April 2008) - Hatemi, G; Silman, A; Bang, D; Bodaghi, B; Chamberlain, A M; Gul, A; Houman, M H; Kötter, I; Olivieri, I; Salvarani, C; Sfikakis, P P; Siva, A; et al.
Abstract : Objectives: To present and analyse the literature sources regarding the management of Behçet disease (BD) identified during the systematic literature research, which formed the basis for the European League Against Rheumatism (EULAR) evidence-based recommendations for the management of BD. Methods: Problem areas and related keywords regarding the management of BD were determined by the multidisciplinary expert committee commissioned by EULAR for developing the recommendations. A systematic literature research was performed using MedLine and Cochrane Library resources through to December 2006. Meta-analyses, systematic reviews, randomised controlled trials (RCTs), open studies, observational studies, case control studies and case series' involving ⩾5 patients were included. For each intervention the effect size and number needed to treat were calculated for efficacy. Odds ratios and numbers needed to harm were calculated for safety issues of different treatment modalities where possible. Results: The literature research yielded 137 articles that met the inclusion criteria; 20 of these were RCTs. There was good evidence supporting the use of azathioprine and ciclosporin A in eye involvement and interferon (IFN)α in mucocutaneous involvement. There were no RCTs with IFNα or tumour necrosis factor (TNF)α antagonists in eye involvement. Similarly controlled data for the management of vascular, gastrointestinal and neurological involvement is lacking. Conclusion: Properly designed, controlled studies (new and confirmatory) are still needed to guide us in managing BD.